2011
DOI: 10.1007/s10443-010-9184-5
|View full text |Cite
|
Sign up to set email alerts
|

Static and Fatigue Behaviour of Hexagonal Honeycomb Cores under In-plane Shear Loads

Abstract: Due to their high specific strength and high specific stiffness properties the use of honeycomb panels is particularly attractive in spacecraft structures. However, the harsh environment produced during the launch of a satellite can subject the honeycomb cores of these sandwich structures to severe quasi-static and dynamic loads, potentially leading to static or early fatigue failures. Knowledge of the static and fatigue behavior of these honeycomb cores is thus a key requirement when considering their use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 12 publications
(8 reference statements)
0
10
0
Order By: Relevance
“…Little fatigue-life data is available for classic-and chiral-auxetic structures [8] and the fatigue-life data of honeycomb structures are mostly available for composite structures with honeycomb cores [9,10]. For this reason a comparison between the low-cycle fatigue properties of the three above-mentioned planar cellular structures has been carried out here.…”
Section: Fig 1 Geometries and Static Failures Of The Planar Cellulamentioning
confidence: 99%
“…Little fatigue-life data is available for classic-and chiral-auxetic structures [8] and the fatigue-life data of honeycomb structures are mostly available for composite structures with honeycomb cores [9,10]. For this reason a comparison between the low-cycle fatigue properties of the three above-mentioned planar cellular structures has been carried out here.…”
Section: Fig 1 Geometries and Static Failures Of The Planar Cellulamentioning
confidence: 99%
“…The fatigue strength is dependent of the kind and amount of adhesive applied but the thickness of face sheet is not influential (Jen et al 2009a,b). The failure mechanisms of composites have been investigated also by in-plane shear load-fatigue tests (Bianchi et al 2012). The fatigue properties of engineered strand lumber and engineered strand panels have been studied and it was demonstrated that these materials could easily survive 10 6 load cycles if loaded to < 40% ultimate strength levels (Eckelman and Winandy 1978).…”
Section: Introductionmentioning
confidence: 99%
“…Pan et al [26,27] analysed the shear buckling of aluminium honeycombs and proposed improved analytical methods for calculating the buckling load. Bianchi et al [28] analysed the nonlinear responses of honeycomb made of aluminium in shear experiments and proposed finite element modelling with initial imperfections. The analysis also focused on their behavior in the orthotropic or off-axis directions.…”
Section: Introductionmentioning
confidence: 99%